2015
DOI: 10.1097/md.0000000000000335
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Observational Study of Pneumococcal Carriage in Children, Their Parents, and Older Adults Following the Introduction of the 7-Valent Pneumococcal Conjugate Vaccine

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
24
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 32 publications
3
24
0
1
Order By: Relevance
“…This vaccine contained the CPS of seven highly virulent serotypes of S. pneumoniae covalently conjugated to the carrier protein, non-toxic diphtheria toxin mutant CRM197 (Table 1). 18 While this conjugate vaccine showed evidence of greater protection in children and herd effect among the population, 19 the effectiveness in adults was not well studied. 5 In 2010, a new conjugate vaccine was released in the United States, Prevnar® PCV13.…”
Section: Characteristics Of the Bacteriummentioning
confidence: 99%
See 1 more Smart Citation
“…This vaccine contained the CPS of seven highly virulent serotypes of S. pneumoniae covalently conjugated to the carrier protein, non-toxic diphtheria toxin mutant CRM197 (Table 1). 18 While this conjugate vaccine showed evidence of greater protection in children and herd effect among the population, 19 the effectiveness in adults was not well studied. 5 In 2010, a new conjugate vaccine was released in the United States, Prevnar® PCV13.…”
Section: Characteristics Of the Bacteriummentioning
confidence: 99%
“…It is estimated that worldwide pneumococcal disease causes 11% of all deaths in children less than five. 19 A study looking at the effects of the PCV7 vaccine noted the risk in this group and the importance of implementing the PCV7 vaccine as PPSV23 was not considered effective in children. 20 …”
Section: Characteristics Of the Bacteriummentioning
confidence: 99%
“…While vaccination of elderly persons has been considered [ 4 ], it has been assumed that immunisation of infants alone may have already resulted in herd immunity, protecting adults against disease caused by vaccine serotypes (VTs) [ 6 ]. However, studies investigating the herd effects of PCVs on serotype carriage in adults are limited and even more rare when elderly are considered [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…pneumoniae from culture very difficult [ 20 , 21 ]. In the scarce recent studies among elderly, the use of swabs usually resulted in carriage being detected in less than 5% of individuals [ 8 , 9 , 22 25 ]. Low rates of nasopharyngeal pneumococcal carriage argue against significant benefits of epidemiological surveillances on colonisation in this age group [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although colonization within the nasal passage often is asymptomatic, access to the airways can result in pneumonia, with further dissemination causing invasive pneumococcal disease (i.e., otitis media, bacteremia, and meningitis) (1,2). Previous studies analyzing the nasopharyngeal culture of 1,704 samples, including children and adults from the same population, revealed that 53% of children carried S. pneumoniae within the nasopharyngeal tract as opposed to only 4 to 11% that were adult carriers (3)(4)(5). Furthermore, S. pneumoniae carriage rates positively correlate with age in young children and then begin to drop in adults (3,6,7).…”
mentioning
confidence: 99%